2015
DOI: 10.1152/jn.00932.2014
|View full text |Cite
|
Sign up to set email alerts
|

Delineation of a frequency-organized region isolated from the mouse primary auditory cortex

Abstract: The primary auditory cortex (AI) is the representative recipient of information from the ears in the mammalian cortex. However, the delineation of the AI is still controversial in a mouse. Recently, it was reported, using optical imaging, that two distinct areas of the AI, located ventrally and dorsally, are activated by high-frequency tones, whereas only one area is activated by low-frequency tones. Here, we show that the dorsal high-frequency area is an independent region that is separated from the rest of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
106
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(116 citation statements)
references
References 84 publications
10
106
0
Order By: Relevance
“…However, the results of the current study clearly shows the presence of dense connections between A2 and the amygdala, while other auditory fields have slight or no connections with the amygdala. Moreover, previous studies have reported that A2 neurons have long latencies (Kubota et al, 2008;Guo et al, 2012;Tsukano et al, 2015), wide bandwidth (Issa et al, 2014;Ohga et al, 2018), and a less-ordered tonotopic arrangement (Issa et al, 2014;Ohga et al, 2018). These data confirm that mouse A2 has properties of a higher-order region, and also support the idea that auditory cortical subregions are functionally specialized in mice (Honma et al, 2013;Baba et al, 2016;Issa et al, 2017).…”
Section: Discussionsupporting
confidence: 85%
“…However, the results of the current study clearly shows the presence of dense connections between A2 and the amygdala, while other auditory fields have slight or no connections with the amygdala. Moreover, previous studies have reported that A2 neurons have long latencies (Kubota et al, 2008;Guo et al, 2012;Tsukano et al, 2015), wide bandwidth (Issa et al, 2014;Ohga et al, 2018), and a less-ordered tonotopic arrangement (Issa et al, 2014;Ohga et al, 2018). These data confirm that mouse A2 has properties of a higher-order region, and also support the idea that auditory cortical subregions are functionally specialized in mice (Honma et al, 2013;Baba et al, 2016;Issa et al, 2017).…”
Section: Discussionsupporting
confidence: 85%
“…This region possesses a weak tonotopic organization (Issa et al, 2014; Tsukano et al, 2015) and, based on our widefield imaging results (Figure 2D and 2G), should be strongly responsive to FM sweeps as well. Indeed, neurons in this field are tuned to high frequencies (Figure 5G) and, more interestingly, respond heterogeneously to sweep rate (Figure 5H).…”
Section: Resultsmentioning
confidence: 68%
“…As for the location of CSR, a nearby “dorsoanterior field” (DA) was found to be responsive to reversals in FM sweep direction (Tsukano et al, 2016, 2015). It remains to be determined if DA and CSR are related since FM sweeps used in those studies included direction reversals and superimposed sweeps and were at their fastest about 5 oct/s, slower than any of the FM stimuli used in this current study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, stimuli with higher frequencies evoked cortical responses in the red colored area. According to recent studies investigating the organization of mouse auditory cortex 30,32,33 , the two to three green areas represent the low frequency field of A1 (A1 LF), the secondary auditory cortex (A2), and the anterior auditory field (AAF). The red area represents the high frequency field of A1 (A1 HF).…”
Section: Resultsmentioning
confidence: 99%